A reactive oxygen species–responsive prodrug micelle with efficient cellular uptake and excellent bioavailability. Issue 7 (2nd February 2018) - Xu, Long; Yang, Yidi; Zhao, Mingying; Gao, Wenxia; Zhang, Hai; Li, Sai; He, Bin; Pu, Yuji
Abstract : Stimuli-responsive polymeric drug delivery systems are of great interest in anticancer research. Here, a reactive oxygen species (ROS)–responsive prodrug was prepared by thioketal linkage of poly(ethylene glycol) (PEG) and the anticancer drug doxorubicin (DOX). Abstract : Stimuli-responsive polymeric drug delivery systems are of great interest in anticancer research. Here, a reactive oxygen species (ROS)–responsive prodrug was prepared by thioketal linkage of poly(ethylene glycol) (PEG) and the anticancer drug doxorubicin (DOX). The ROS–responsive property of the prodrug was confirmed by dynamic light scattering and 1 H NMR. The prodrug was then used as a drug carrier to further load DOX, to form a DOX-loaded prodrug micelle, which showed dual ROS and pH-responsive release behaviors. The prodrug micelle exhibited rapid intracellular uptake. Interestingly, the in vitro anticancer activity of the ROS–responsive prodrug micelle was better than that of the DOX-loaded prodrug micelle because of its faster cellular uptake and better bioavailability. However, both the ROS–responsive prodrug and drug-loaded prodrug micelles showed better anticancer efficacy than a non-responsive DOX-loaded poly(ethylene glycol)- block -polycaprolactone (PEG2k-PCL5k) micelle. Consistent results were obtained in in vivo animal experiments as the antitumor efficacy of the prodrug micelle was superior to that of the DOX-loaded prodrug micelle. Both micelles showed negligible systemic toxicity in vivo .